Impact of Project Control on Project Success with Mediating Effects of Project Governance - Hafiz Fawad Ullah; Rizwan Khan; Waqas Amin; Bilal Khan, (Dialogue Social Science Review (DSSR), 2024)
Project success is the accomplishment of project activities within specific time, cost, quality and scope. Every project manager puts his/her efforts in order to achieve these goals. Activities relating to monitoring and controlling are essential to achieve the project success. Different factors like time, cost, and scope are the factors that are kept under review from the beginning till end of the project to make sure the project success is achieved. Thus, the main aim of this study was to examine the effects of project control on project success with mediating effects of project governance. Quantitative method was used in this study. In survey method, for data collection the study used pre-structured questionnaire. Total number of questionnaires distributed was 300 and linear regression and mediation analysis were used in SPSS. The findings suggested that there are positive and significant effects of project control are available on project success and the findings also investigated that project governance had partial mediation analysis. This research could work as the foundation for the other scholars as well as it can be utilized in construction sector projects for planning and controlling purposes.